Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
ho dang khai
Xem chi tiết
Anh Duc
Xem chi tiết
Trâm Anh
Xem chi tiết
Võ Đông Anh Tuấn
5 tháng 9 2016 lúc 9:00

\(\frac{a^2+b^2}{c^2+d^2}=\frac{ab}{cd}\)

\(\Leftrightarrow\left(a^2+b^2\right)cd=\left(c^2+d^2\right)ab\)

\(\Leftrightarrow a^2cd-c^2ab-d^2ab+b^2cd=0\)

\(\Leftrightarrow ac\left(ad-bc\right)-bd\left(ad-bc\right)=0\)

\(\Leftrightarrow\left(ac-bd\right)\left(ad-bc\right)=0\)

\(\Leftrightarrow\begin{cases}ac=bd\\ad=bc\end{cases}\)

\(\Leftrightarrow\begin{cases}\frac{a}{b}=\frac{c}{d}\\\frac{a}{b}=\frac{d}{c}\end{cases}\)

 

Nguyễn Ngọc Huyền Như
Xem chi tiết
Sakura Kinomoto
Xem chi tiết
The magic
Xem chi tiết
Nguyễn Tấn Phát
8 tháng 7 2019 lúc 10:33

Cho \(\frac{a}{b}=\frac{c}{d}=k\Rightarrow\hept{\begin{cases}a=bk\\c=dk\end{cases}\Rightarrow\hept{\begin{cases}a^2=b^2k^2\\c^2=d^2k^2\end{cases}}}\)

Ta có: \(\frac{a^2+b^2}{c^2+d^2}=\frac{b^2k^2+b^2}{d^2k^2+d^2}=\frac{b^2\left(k^2+1\right)}{d^2\left(k^2+1\right)}=\frac{b^2}{d^2}\)

Lại có: \(\frac{a.b}{c.d}=\frac{bk.b}{dk.d}=\frac{b^2k}{d^2k}=\frac{b^2}{d^2}\)

Vậy \(\frac{a^2+b^2}{c^2+d^2}=\frac{a.b}{c.d}\left(ĐPCM\right)\)

🎉 Party Popper
8 tháng 7 2019 lúc 10:35

\(\frac{a^2+b^2}{c^2+d^2}=\frac{ab}{cd}\)

<=> a2cd + b2cd = abc2 + abd2

<=> a2cd - abd2 = abc2 - b2cd

<=> ad(ac - bd)  = bc(ac - bd) 

<=> ad = bc

<=> \(\frac{a}{b}=\frac{c}{d}\)

\(\frac{a^2+b^2}{c^2+d^2}=\frac{ab}{cd}\)

\(a^2cd+b^2cd=abc^2+abd^2\)

\(a^2cd-abd^2=abc^2-b^2cd\)

\(ad\left(ac-bd\right)=bc\left(ac-bd\right)\)

\(ad=bc\)

\(\frac{a}{b}=\frac{c}{d}\)

Saitou Yakumo
Xem chi tiết
Soke Soắn
Xem chi tiết
Trần Minh Hoàng
13 tháng 7 2018 lúc 11:33

Đặt \(\dfrac{a}{b}=\dfrac{c}{d}=k\Rightarrow\left\{{}\begin{matrix}a=bk\\c=dk\end{matrix}\right.\)

Ta có:

\(\dfrac{ab}{cd}=\dfrac{bk.b}{dk.d}=\dfrac{b^2}{d^2}\) (1)

\(\dfrac{a^2-b^2}{c^2-d^2}=\dfrac{\left(bk\right)^2-b^2}{\left(dk\right)^2-d^2}=\dfrac{b^2k^2-b^2}{d^2k^2-d^2}=\dfrac{b^2\left(k^2-1\right)}{d^2\left(k^2-1\right)}=\dfrac{b^2}{d^2}\) (2)

Từ (1) và (2) suy ra \(\dfrac{ab}{cd}=\dfrac{a^2-b^2}{c^2-d^2}\)

Đặng Trọng Đưc
Xem chi tiết
zZz Cool Kid_new zZz
28 tháng 7 2019 lúc 17:23

Viet lai de bai

Cho \(\frac{a}{b}=\frac{c}{d}\)

CMR:\(\frac{ab}{cd}=\frac{a^2+b^2}{c^2+d^2}\)

Bai lam:

Dat \(\frac{a}{b}=\frac{c}{d}=k\)

\(\Rightarrow a=bk;c=dk\)

Ta co:

\(\frac{a^2+b^2}{c^2+d^2}=\frac{b^2k^2+b^2}{d^2k^2+d^2}=\frac{b^2\left(k^2+1\right)}{d^2\left(k^2+1\right)}=\frac{b^2}{d^2}\)

\(\frac{ab}{cd}=\frac{bk\cdot b}{dk\cdot d}=\frac{b^2k}{d^2k}=\frac{b^2}{d^2}\)